Association of Stress, Glucocorticoid Receptor, and FK506 Binding Protein Gene Polymorphisms With Internalizing Disorders Among HIV-Infected Children and Adolescents From Kampala and Masaka Districts-Uganda - Tonny Jimmy Owalla; Tonny Jimmy Owalla; Wilber Joseph Ssebajjwe; Dennis Muhanguzi; Jacqueline Samantha Womersley; Jacqueline Samantha Womersley; Eugene Kinyanda; Eugene Kinyanda; Allan Kalungi; Allan Kalungi (Frontiers Media S.A., 2021)
Children and adolescents living with human immunodeficiency virus (CA-HIV) suffer a considerable burden of internalizing disorders (IDs; depressive and anxiety disorders). Environmental and genetic factors have been reported to influence the vulnerability to IDs in western settings; however, their role among African populations remains inadequately explored. We investigated the individual and interactive effects of stress and single-nucleotide polymorphisms within the FK506 binding protein 5 (rs1360780) and glucocorticoid receptor (rs10482605) genes on ID status in a cohort of CA-HIV in Uganda. We genotyped rs10482605 (309 cases and 315 controls) and rs1360780 (350 cases and 335 controls) among CA-HIV with and without IDs using Kompetitive Allele-Specific PCR. Socio-demographic variables, as well as allele and genotype distributions, were compared between cases and controls using chi-square tests. Genotypes were assessed for Hardy-Weinberg equilibrium. Composite indices of recent and chronic stress classes were also generated. A hierarchical cluster analysis was used to generate cutoff points within each of the indices of recent and chronic stress. Logistic regression was used to assess the association between IDs and each of recent stress, chronic stress, and the investigated genotypes. The interaction effect of chronic/recent stress on the association between each of the polymorphisms and IDs was determined using a likelihood ratio test. We observed no significant association between IDs and rs1360780 and rs10482605 polymorphisms within the FKBP5 and glucocorticoid receptor genes, respectively (P > 0.050). Severe recent stress increased the vulnerability to IDs among CA-HIV (P = 0.001). We did not observe any gene-environment effect on vulnerability to IDs in this population. These findings support the currently held opinion that polymorphisms at single genetic loci only contribute a very small effect to the genetic vulnerability to IDs.